Four-year analysis of high-risk human papillomavirus infection among women in rural areas of Nyingchi City, Tibet - Li, Jianqi; Li, Xiaojie; Sheng, Xiujie (Frontiers in Public Health, 2023)
Purpose This study aims to address the existing data gap regarding the status of high-risk human papillomavirus (HR-HPV) infection and the distribution of HR-HPV subtypes among women in rural areas of Nyingchi City, Tibet. The research objectives include providing insights for HPV vaccine development. Methods The research collected data from two rounds of cancer screening conducted among rural women in Nyingchi City, Tibet, from 2019 to 2022. HR-HPV subtype gene detection was performed using the PCR fluorescence method on the collected samples. And then analyzed the HR-HPV infection rate among rural women in Nyingchi City, Tibet, as well as the infection rate of different HR-HPV subtypes and their distribution across different age groups. A comparison was made between the infection rates of women in rural areas outside the Qinghai-Tibet Plateau and those in Nyingchi City. Results A total of 15,687 cases included. The overall HR-HPV infection rate among women in rural areas of Nyingchi City, Tibet, was 13.00% (2040/15,687), which was significantly higher than the rate among women in rural areas outside the Qinghai-Tibet Plateau (7.82% (9,249/118,237); χ2 = 635.7, p < 0.001). The highest HPV infection rate was observed in the 35–39 age group, with a rate of 15.31% (499/3260), which was significantly higher than the rate of 7.22% (1827/25,322) among women in the same age group in rural areas outside the Qinghai-Tibet Plateau (χ2 = 253.00, p < 0.001). The lowest HPV infection rate was found in the 50–54 age group, with a rate of 9.69% (246/2540), which was statistically different from the rate of 8.14% (1,604/19,698) among women in the same age group outside the Qinghai-Tibet Plateau (χ2 = 17.68, p < 0.001). The top three HR-HPV subtypes among women in rural areas of Nyingchi City, Tibet, were HPV52 (20.15%, 411/2040), HPV16 (12.45%, 254/2040), and HPV58 (11.96%, 244/2040). These findings align with the top three HR-HPV subtypes among women in rural areas outside the Qinghai-Tibet Plateau. Furthermore, the top three HR-HPV subtypes among women aged 35–39, 40–44, and 45–49 in rural areas of Nyingchi City, Tibet, were HPV52, HPV16, and HPV58. In conclusion, the HR-HPV infection rate among women in rural areas of Nyingchi City, Tibet, is significantly higher compared to women in rural areas outside the Qinghai-Tibet Plateau, with consistent patterns observed in the distribution of the top three HR-HPV subtypes between the two regions.